Enrollment of Vector in Cardiology and Study of Cardiac Cadence - Mishra, Sujal; Sahani, Suresh Kumar; Sahani, Kameshwar; Sah, Binod Kumar; Singh, Vijay Vir (Asian Journal of Science, Technology, Engineering, and Art, 2024)
We have analyzed the application of vectors in cardiology and the way cardiac vector theory analyzes the heartbeat and can explain the entire cardiac conduction vector relationship and the Enthoven equilateral triangle hypothesis. This sheet explains the principles of the electrocardiogram and the interpretation of the waveforms. ECG can be called an electrocardiogram, which is a process of producing electrical activity through repetitive cycles. This diagram shows the voltage and duration of electrical activity by placing electrodes on the skin. Vector cardiography ( VCG) is a procedure that creates a 2D image of the heart's electrical activity by monitoring the spatial location of ECG waves at each successive point in their period. Even in the 21st century, coronary heart disease still represents a serious threat to humans and a major challenge to the scientific community. The most important elements for understanding and interpreting the ECG are the Enthoven triangle and the cardiac vector hypothesis, which have the potential , saving millions of lives when used quickly and appropriately to treat patients.